PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SDN 196 SUKARASA KOTA BANDUNG - Citra Lestari; Tatang Syarifudin; Amilah Sariandini (STKIP Subang, 2023)
The background of this study is the low writing skills of students, especially in writing narrative essay writing skills. This research was conducted in class IV SDN 196 Sukarasa, Bandung. The learning model applied is the Project Based Learning model. The research method used in this research is Classroom Action Research which consists of two cycles, where each cycle consists of two meetings. The purpose of this research is to design a narrative essay writing lesson through the application of a project based learning (PJBL) model for fourth grade students at SDN 196 Sukarasa, Bandung City; To determine the increase in project-based learning outcomes (PJBL) can improve the skills of writing narrative essays in grade 4 students at SDN 196 Sukarasa, Bandung City. Research data obtained through observation and assignment. From the results of this study it can be concluded that the application of the Project Based Learning model can improve the skills of writing narrative essays to increase, it can be seen from the results of student learning completeness in the pre-cycle or initial test obtained 5 students or 23% who achieved 23% mastery in the pre-cycle before implementing the model learning Project Based Learning (PJBL) increased by 54% to 77% in cycle I with the application of the Project Based Learning (PJBL) learning model and experienced an increase of 12%, namely 89% in cycle II. Of the 22 students, there were 5 students who had not achieved completeness in cycle I and in cycle II it decreased so that all students achieved completeness.